Native oxide and hydroxides and their implications for bulk AlN crystal growth - Edgar, James H.; Du, L.; Lee, R. G.; Nyakiti, L.; Chaudhuri, J. (My University, 2008)
Oxygen degrades the properties of AlN, thus producing bulk single crystals with low oxygen concentrations is an important goal. Most of the oxygen in bulk AlN single crystals grown by the sublimation-recondensation method originates from the hydroxides and oxides that spontaneously form on the surfaces of the AlN source powder. For a typical AlN powder with an average particle size of 1-2 microns, a 1-3 nm thick oxide and/or hydroxide can account for most of its oxygen (generally on the order of 1.0 wt%) and hydrogen (200-300 ppm). Heating the AlN powder source at 1950 °C for 10 h in a nitrogen atmosphere reduced its surface area by a factor of 160 (due to sintering), the oxygen concentration by 16, and the hydrogen concentration by 67. The difference in these reduction factors suggests some of the oxygen is dissolved into the bulk AlN with this heat treatment. By first annealing the AlN powder at a low temperature (950-1000 °C) for several hours before sintering at 1950 °C, the oxygen and hydrogen concentrations were reduced to lower levels. The low temperature treatment is effective eliminating oxygen and hydrogen from the surface of the powder, while high temperature sintering reduces the specific surface area of the source. The combination of heat treatments produced a source with oxygen and hydrogen concentrations as low as 0.015 wt% O (1.9 x 10[superscript]19 atoms O cm[superscript]-3) and 1.7 ppm H (3.4 x 10[superscript]18 atoms H cm[superscript]-3). Annealing becomes less effective at removing oxygen and hydrogen with longer heat treatments, suggesting there is a minimum oxygen concentration that can be produced with this method.
Keywords: Impurities; Purification; Growth from vapors; Nitrides; Semiconducting aluminum compounds